A non-tracking concentrating collector for solar thermal applications. (15th August 2017) - Ratismith, Wattana; Favre, Yann; Canaff, Maxime; Briggs, John
Highlights: A non-tracking solar collector of novel design is tested outdoor in SE Asia. A novel performance parameter, the power concentration factor, is introduced. The header pipe has a new "wet" connection giving enhanced efficiency. The collector is superior to a commercially-available non-concentrating collector. Abstract: We report the development of a solar thermal collector module based on our proposed design (Ratismith et.al., 2014) of a large acceptance-angle multiple-parabolic trough which surrounds a standard evacuated cylindrical tube containing a planar absorber plate. The concentrator accepts diffuse solar radiation with an intercept factor of near 100% and so is suitable particularly for tropical climates. The module incorporates a novel direct metal-to-water contact resulting in an improved efficiency of heat transfer to the working liquid. Comparison with the performance characteristics, principally power output and temperatures attained, of a commercially-available non-concentrating assembly of evacuated absorber tubes is made. The experimental results, obtained by testing under typical conditions of solar irradiation throughout the day in Bangkok, indicate that the improvement over a non-concentrating collector, suggested theoretically on the basis of ray-tracing studies, is attained in practice. The superior performance of the concentrating collector indicates its suitability both for residential and industrial applications.